Doctrine of Caveat Emptor (Buyer be aware) in Common Law and the Doctrine of Khiyar al aib (Option of defect) in Islamic Law: A Comparative Study - Malek, Abdul; Begum, Anju Man Ara; Hoque, Kazi Arshadul (IIUC Studies, 2016)
The Sale of Goods Act, 1930 deals with one of the important branches of contract especially the moveable goods with which the general people in the world deal every day. In dealing with the goods proposed for sale must be free from any known or unknown defect of either party of the contract of sale. Regarding the sale of defective goods the buyer has some remedies against the default seller in both common law and Islamic law. In common law it is known as Caveat Emptor (Buyer be aware) and in Islamic law it is known as Khiyar al aib (Option of defect). It is the general rule that the buyer should have an opportunity to satisfy himself as to the quality of the goods for his particular purpose and in absence of any query or unskilled test by the buyer, the seller is not to be liable for anything. In this article efforts have been made to examine the rights and duties of buyer and seller in Common law and Islamic Law. An attempt has also been made to find out similarities and dissimilarities of both laws regarding caveat emptor. Thus the paper, through the analysis of both laws, tries to address the problems and solutions related to caveat emptor. IIUC Studies Vol.10 & 11 December 2014: 201-216